2011
DOI: 10.1016/j.jaapos.2011.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Validity of plusoptiX S04 photoscreener as a vision screening tool in children with intellectual disability

Abstract: abnormal neuro-imaging have normal retinas. Patients with only nonskull fractures are unlikely to have retinal hemorrhages. Conclusions: In our population, evaluation for NAT should include both neuro-imaging and DFE, as DFE alone would miss a large portion of patients. Patients with isolated fractures may be considered low-risk for retinal hemorrhages.048 Intraocular pressure spike after secondary IOL implantation in aphakic glaucoma. John H. Boden, Casey Mickler, Rupal H. Trivedi, M. Edward Wilson Purpose: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Photoscreeners and hand-held autorefractometers have been used for screening refractive errors, and several studies were conducted to compare devices in healthy school-aged children and also some speci c patient populations, including autism and intellectual disability [18,19,7]. However, there was no study comparing non-cycloplegic measurements of photoscreeners and hand-held autorefractometers with cycloplegic measurements in children with ADHD in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoscreeners and hand-held autorefractometers have been used for screening refractive errors, and several studies were conducted to compare devices in healthy school-aged children and also some speci c patient populations, including autism and intellectual disability [18,19,7]. However, there was no study comparing non-cycloplegic measurements of photoscreeners and hand-held autorefractometers with cycloplegic measurements in children with ADHD in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The Plusoptix was found very useful compared with cycloplegic retinoscopy, especially in determining axis and cylinder power in various studies [20]. Ugurbas et al evaluated the validity of Plusoptix S04 as a vision screening device and reported that non-cycloplegic measurements of the device are accurate for children with intellectual disability [18]. Furthermore, in a study by McCurry et al, it was reported that vision screening with Plusoptix S08 reduced the full ophthalmologic examination requirement in one-third of the screening children with autism [19].…”
Section: Discussionmentioning
confidence: 99%
“…Photoscreeners and hand-held autorefractometers have been used for screening refractive errors, and several studies were conducted to compare devices in healthy school-aged children and also some specific patient populations, including autism and intellectual disability [7,21,22]. However, there was no study comparing non-cycloplegic measurements of photoscreeners and hand-held autorefractometers with cycloplegic measurements in children with ADHD in the literature.…”
Section: Studies Investigating the Visual Function And Ocular Abnorma...mentioning
confidence: 99%
“…The Plusoptix was found very useful compared with cycloplegic retinoscopy, especially in determining axis and cylinder in various studies [23]. Ugurbas et [21] evaluated the validity of Plusoptix S04 as a vision screening device and reported that non-cycloplegic measurements of the device are accurate for children with intellectual disability.…”
Section: Studies Investigating the Visual Function And Ocular Abnorma...mentioning
confidence: 99%